1999
DOI: 10.1042/bj3410015
|View full text |Cite
|
Sign up to set email alerts
|

A single point mutation leads to an instability of the hetero-octameric structure of yeast phosphofructokinase

Abstract: Yeast phosphofructokinase is an oligomeric enzyme whose detectable activity in vitro depends on its hetero-octameric structure. Here we provide data demonstrating that an alanine residue at positions 874 (for the PFK1-encoded α-subunit) or 868 (for the PFK2-encoded β-subunit) is crucial to achieve this structure. Thus subunits carrying substitutions by either aspartate or lysine of this residue cause a lack of phosphofructokinase activity in vitro and signals of the subunits are poorly detectable in Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For example, research on yeast phosphofructokinase identified mutations that modified allosteric regulation (116,167,296). Nonetheless, there are only a few recent examples of yeast metabolic engineering that take advantage of site-specific enzyme mutagenesis to modify regulatory properties.…”
Section: In Vivo Protein Activitymentioning
confidence: 99%
“…For example, research on yeast phosphofructokinase identified mutations that modified allosteric regulation (116,167,296). Nonetheless, there are only a few recent examples of yeast metabolic engineering that take advantage of site-specific enzyme mutagenesis to modify regulatory properties.…”
Section: In Vivo Protein Activitymentioning
confidence: 99%
“…It is also likely that the Pfk produced in the mutants is still a heterooctamer, since a loss of the quaternary structure in the yeast enzyme usually results in aggregation and degradation of the subunits, leading to a drastic decrease in Western blot signals (see Ref. 43, and references therein), which is not observed in the PFKatp mutants. Given these data, it is not surprising that the mutant strains did not show any obvious defect for growth on glucose media or in respect to glycolytic flux.…”
Section: Fig 5 Heat Inactivation Of Pfk From Different Mutant Strainsmentioning
confidence: 99%
“…Identical amounts of total protein obtained from three independent experiments of untreated and zymocin-arrested cells were subjected to SDS-PAGE analysis using 6% gels, electroblotted onto polyvinylidene difluoride membranes (Immobilon), and probed with mouse monclonal anti-pol IIA and anti-pol II0 antibodies 8WG16 and H14 (Covance). Protein loadings were compared using a polyclonal rabbit antibody directed against the ␣-and ␤-subunits of yeast Pfk1p (33). pol II quantitation used the Image Master 2D (Amersham Biosciences) program.…”
Section: Methodsmentioning
confidence: 99%
“…Protein loading was followed using a polyclonal antiserum specific for the ␣-and ␤-subunits of phosphofructokinase 1 (Pfk1p) (33). B, identical protein amounts obtained from cell fractionation of untreated cells and cells arrested with zymocin for 3 h were subjected to 6% SDS-PAGE and immunoprobed with antibodies specific for IIA and II0 (see A).…”
Section: Fig 3 Effect Of Zymocin Application On Pol II Phosphorylatmentioning
confidence: 99%